Bioactive Polyphenols from Wine Grapes - Stuart, Jeffrey A.; Robb, Ellen L.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Is red wine good for you? And if so, why? How much? And what are the actual benefits? This addition to the SpringerBriefs in Cell Biology series thoroughly but succinctly answers these questions. It covers the biochemistry, health benefits and therapeutic potential of wine grapes.  It begins with  an overview of phytoalexin production in Vitis vinifera (Common Grape Vine), detailing the relationship of resveratrol to analogues such as pterostilbene, piceid and the viniferins (resveratrol oligomers).    The discussion then turns to the hundreds of reports linking resveratrol and related grape vine polyphenols to various beneficial health effects especially cardio- and cerebro- vascular, metabolic, anti-inflammatory and more.  Also addressed are the numerous intracellular mechanisms that have been shown to mediate the effects of these compounds in mammalian cells and tissues.  Finally, the authors discuss aspects of polyphenol bioavailability and how this will influence choices taken for delivering these compounds as nutritional supplements.  A brief chapter containing general conclusions and prospectus rounds out the information.
Resveratrol and its Derivatives as Phytoalexins -- Health Effects of Resveratrol and its Derivatives -- Cellular and Molecular Mechanisms of Resveratrol and its Derivatives -- Bioavailability of Resveratrol, Pterostilbene, and Piceid -- General Discussion and Future Considerations.
Keywords: Cell biology; Plant biochemistry; Enzymology; Cell Biology; Plant Biochemistry; Enzymology